Penerapan Terapi Musik Klasik untuk Mengurangi Gangguan Pola Tidur pada Pasien Penyakit Jantung Koroner Ny. M: Penerapan Terapi Musik Klasik untuk Mengurangi Gangguan Pola Tidur - christine Anastasya Bamotiwa; Nova Natalia Beba (Yayasan Ekselensi Daya Indonesia, 2025)
Abstract Coronary heart disease is a disease caused by plaque that builds up in the coronary arteries which supply oxygen to the heart muscle which causes the sufferer to experience sleep disturbances, so music therapy is given. Music therapy is a therapy that uses music as a way to reduce sleep disorders experienced by the patient. where music therapy provides a therapeutic effect for those who listen to it. The descriptive case study research design included 1 respondent, and data collection was done through interviews, observation, and physical examination. The instruments used were PSQI assessment format, general assessment format, informed consent, and objects in cellphones and headsets. The data analysis used is data reduction, presentation, and conclusions. The intervention carried out was classical music therapy. After carrying out nursing actions for 3 meetings in 1 week, it was found that the client's sleep quality improved and the problem was resolved with sleep. PSQI results before therapy were 9 (medium sleep quality) and after therapy 5 (good sleep quality) and the client became more relaxed and slept better. This case study concludes that sleep quality has improved. Classical music therapy can be applied to the elderly by considering the type of sleep quality, length, and time of administration so that it is truly effective in overcoming sleep pattern disorders